Greener and cheaper: green monetary policy in the era of inflation and high interest rates - Nicolás Aguila; Joscha Wullweber (Eurasian Economic Review, 2024)
In recent years central bankers have devoted increased attention to the question of whether and how to intervene to address the growing environmental and climate crisis. The climate intervention debate gained momentum during a period of low inflation and loose monetary policy in core economies – a time characterised by near zero interest rates and large asset purchase programmes. Since 2021, however, the macroeconomic context has changed. Against this background, the paper analyses the contradictory and problematic nature of the direction monetary policy has taken in reaction to higher inflation. It argues that higher interest rates delay the green transformation by raising the cost of sustainable investments, and that the resulting delay also hampers prospects for achieving price stability. The paper concludes that the present macroeconomic environment demands a `greener and cheaper' monetary policy approach designed to address the environmental and climate crisis and also to simultaneously fight inflation.
Keywords: E50; E52; Q58; 330; Green monetary policy; Central banking; Inflation; Price stability; Interest rates; Environmental and climate risks